Analysis of Robot Dynamics and Compensation Using Classical and Computed Torque Techniques - Machado, J. A. Tenreiro (1993)
A classical analysis of the dynamics of robot manipulators is presented. It is shown that these systems have configuration-dependent properties and can be open-loop unstable. Due to this fact, present day linear controllers are inefficient. On the other hand, nonlinear hardware and software compensation methods also are shown to have some limitations. Controllers based on the direct design algorithm and the computed torque method have superior performances. These algorithms have nonlinear loops, yet it is shown that a linear analysis is still feasible. Therefore, classical design tools can be adopted in order to develop practical implementations